2015
DOI: 10.1038/ncomms9677
|View full text |Cite
|
Sign up to set email alerts
|

Embryo-scale tissue mechanics during Drosophila gastrulation movements

Abstract: Morphogenesis of an organism requires the development of its parts to be coordinated in time and space. While past studies concentrated on defined cell populations, a synthetic view of the coordination of these events in a whole organism is needed for a full understanding. Drosophila gastrulation begins with the embryo forming a ventral furrow, which is eventually internalized. It is not understood how the rest of the embryo participates in this process. Here we use multiview selective plane illumination micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
218
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(233 citation statements)
references
References 48 publications
15
218
0
Order By: Relevance
“…The folding of the mesoderm in the Drosophila embryo has been suggested to result from the buckling of a homogeneous epithelium under compression, based on lateral vertex model simulations resulting in buckled shapes reminiscent of the invaginating embryo [37]. Alternatively, difference in apical and basal tension in the mesoderm can drive tissue invagination, depending on the passive elastic properties of the cells and on the stiffness of the surrounding material [38,39]. The effect of the basement membrane elasticity on folds in flat epithelia induced by apico-basal tension asymmetry has also been discussed [40] (figure 2 c ).…”
Section: Applications Of Vertex Modelsmentioning
confidence: 99%
“…The folding of the mesoderm in the Drosophila embryo has been suggested to result from the buckling of a homogeneous epithelium under compression, based on lateral vertex model simulations resulting in buckled shapes reminiscent of the invaginating embryo [37]. Alternatively, difference in apical and basal tension in the mesoderm can drive tissue invagination, depending on the passive elastic properties of the cells and on the stiffness of the surrounding material [38,39]. The effect of the basement membrane elasticity on folds in flat epithelia induced by apico-basal tension asymmetry has also been discussed [40] (figure 2 c ).…”
Section: Applications Of Vertex Modelsmentioning
confidence: 99%
“…Apical constriction in these cells promotes invagination of the prospective mesoderm, and leads to the formation of the ventral furrow (Martin et al, 2009; Polyakov et al, 2014; Rauzi et al, 2015). We have previously shown that ROCK is enriched in the center of the apical domain (medioapical), displaying a type of cell polarity we termed radial cell polarity, in which proteins are polarized along the radial axis from the centroid to cell edge (Mason et al, 2013; Vasquez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both the spatial and temporal resolutions required to follow tissue and organ development in four‐dimensions are now accessible, as shown in Figure and in Movie S1, and see (Rauzi et al . ). Such approaches have also been used in the larva to explore brain function (Lemon et al .…”
Section: Discussionmentioning
confidence: 97%